A review of the genus Takecallis Mastumura in Korea with the description of a new species (Hemiptera, Aphididae) - Yerim Lee; Seunghwan Lee (ZooKeys, 2018)
The aphid genus, Takecallis Mastumura, 1917, was reviewed from Korea. Four species, T. alba Y. Lee, sp. n., T. arundicolens (Clarke), T. arundinariae (Essig), and T. taiwana (Takahashi), are recognized in Korea and morphological and molecular evidence are presented. Species descriptions and illustrations are given for the four species. A key to Korean species and the results of COI sequence analyses are also provided.